Citrullus colocynthis: source of biodiesel - Benaissa , Asmaa (Algerian Journal of Biosciences, 2022)
Citrullus colocynthis (L.). Schrad, is a member of the botanical family of Cucurbitaceae and is commonly called coloquinte or "desert gourd", Handhal (Arabic) or Alkad (Tamahaq). This plant is known for its high oil content, it is a source of biodiesel and a real substitute for conventional diesel. Biodiesel is defined as a chemical alteration of vegetable oil to match the characteristics of the engine. The transesterification reaction is the most common method for converting coloquinte oil into esters and glycerol. The purpose of this communication is to draw attention to the biodiesel produced by coloquinte, which has been widely described in the literature.